Study of pathogenesis and immune response at experimental infection of broiler chicks with avian metapneumovirus subtype В - M. A. Volkova; P. S. Yaroslavtseva; V. Yu. Sosi Pato Rova; T. L. Eroshina; I. A. Chvala (Ветеринария сегодня)
Experimental infection of 7-day-old chicks with the isolate of avian metapneumovirus Subtype В induced mild signs of respiratory infection and swelled infraorbital sinuses in 5-15 days post infection. Lesions in tissues of trachea, nasal passages and primary lymphoid organs were reported. Using real-time RT-PCR avian metapneumovirus genome was detected in the upper part of the respiratory tract, infraorbital sinuses and Harderian gland within 2-12 days post infection. The immune response was characterized by formation of humoral and local antibodies in 7-21 days post infection. In 3 days post infection increased percentage of CD8a+ T-cell subpopulation was reported in blood and spleen of the infected chicks.